Mesenteric Adenitis Caused by Salmonella Typhi: A Case Report - Nik Hashim, Nik Haszroel Hysham; Che Azmi, Nur Ain (IIUM Medical Journal Malaysia, 2021)
Both mesenteric adenitis and acute appendicitis may present with fever and right lower quadrant pain. This presentation makes it challenging to provide a timely and accurate diagnosis to avoid unnecessary surgery. We report a case of an 8-year-old who was admitted with fever and right lower quadrant pain, loss of appetite, and diarrhoea. There were tenderness and rigidity in the right lower quadrant of the abdomen. Hepatomegaly was present. Full blood count showed pancytopenia, and serum transaminases were mildly elevated. The clinical features in typhoid fever are not specific, making it difficult to differentiate from other infectious causes such as malaria, dengue, or leptospirosis, common in the region. This report illustrates a rare case of mesenteric adenitis caused by Salmonella serotype Typhi. It also shows the benefit of doing an abdominal ultrasound to help the surgeon decide whether surgery is necessary.